1,3 β-D-Glucan versus blood culture for the diagnosis of invasive fungal infection in formula-fed preterm neonates - Awad, H A; Ismail, R I H; Elbadrawy, M A (QJM : An International Journal of Medicine, 2020)
Abstract Background 1,3 β-D-Glucan is an important marker for diagnosis of invasive fungal infection (IFI).Its value in comparison to blood culture is not yet established in neonates. Aim primary aim is to study the value of 1,3 β-D-Glucan in comparison with culture on Sabouraud dextrose agar in diagnosis of IFI, Secondary aim is to study the prevalence of IFI in preterm neonates. Subjects and methods a prospective observational study carried on 75 non-exclusively breast fed preterm neonates ≤34 weeks gestational age. Tollner and Rodwell sepsis scores, SNAPII and blood culture were done to all neonates initially and on day 10&17 of life. 1,3 β-D-Glucan was done for all neonates on day 10 of life. Results fungal growth was found in 9.3% of included preterm neonates.1,3β-D-Glucan was higher in culture proven fungal sepsis compared to culture proven bacterial sepsis and culture negative preterm neonates (83.28±26.22 pg\ µl, 51.42±16.71 pg\ µl, 43.07±12.87 pg\ µl respectively). 1,3 β-D-Glucan was related to Tollner (r = 0.286,p=0.013), Rodwell (r = 0.317,p=0.006) sepsis scores and to SNAPII score (r = 0.331,p=0.04). Its cut off point for diagnosis of IFI is 79pg\µl with sensitivity of 71% and specificity of 98%. Conclusion 1,3β-D-Glucan is an easy, rapid and specific marker for diagnosis of IFI in neonates. Further studies are needed to evaluate it as a therapeutic monitoring for IFI.